2015
DOI: 10.1088/1367-2630/17/2/023061
|View full text |Cite
|
Sign up to set email alerts
|

Current-induced magnetic skyrmions oscillator

Abstract: Spin transfer nano-oscillators (STNOs) are nanoscale devices which are promising candidates for onchip microwave signal sources. For application purposes, they are expected to be nano-sized, to have broad working frequency, narrow spectral linewidth, high output power and low power consumption. In this paper, we demonstrate by micromagnetic simulation that magnetic skyrmions, topologically stable nanoscale magnetization configurations, can be excited into oscillation by a spin-polarized current. Thus, we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
152
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(160 citation statements)
references
References 47 publications
5
152
2
1
Order By: Relevance
“…2a,b). The gyrofrequency (11) is determined by the exchange stiffness A, intrinsic DMI parameter D, the perpendicular anisotropy constant K, as well as the dot saturation magnetization and radius R. The recent simulations by Zhang et al 33 of the gyrotropic dynamics of the skyrmion in a free layer of circular nanopillar are in qualitative agreement with Eq. (11).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…2a,b). The gyrofrequency (11) is determined by the exchange stiffness A, intrinsic DMI parameter D, the perpendicular anisotropy constant K, as well as the dot saturation magnetization and radius R. The recent simulations by Zhang et al 33 of the gyrotropic dynamics of the skyrmion in a free layer of circular nanopillar are in qualitative agreement with Eq. (11).…”
Section: Resultssupporting
confidence: 60%
“…Additional reason for that are perspective applications of the RT isolated skyrmions in nanoscale devices 33 . Isolated skyrmions, conditions required for their existence in patterned films [11][12][13][14]23,34,35 , and the dynamics of isolated skyrmions in magnetic films and nanodots have been simulated 29,33,36,37 and experimentally explored 38 . Lin et al 29 simulated dynamics of isolated skyrmion in an infinite film and found one gyrotropic mode, several breathing and non-symmetric skyrmion shape modes in the area of the skyrmion stability.…”
Section: Introductionmentioning
confidence: 99%
“…27 The dynamics of coupled skyrmions 28 and collective excitation 29 were considered as well. The spintronic application of skyrmion-based spin transfer nano-oscillator (STNO) was proposed 30 . In this Letter, we numerically study collective skyrmion dynamics in the chain of the magnetic nanodots with skyrmion texture.…”
Section: 2mentioning
confidence: 99%
“…Indeed, the magnetic skyrmion as information carrier attracts increasing interest for developing the nextgeneration data storage devices due to its remarkable stability, extremely small size, and low-current depinning property [21][22][23][24][25][26][27][28][29][30] . Concurrently, many other applications of the magnetic skyrmions have been proposed and demonstrated, such as skyrmion-based logic devices 31 , oscillators 32,33 , and electronic devices [34][35][36] .…”
Section: Introductionmentioning
confidence: 99%